Shadow Writing. W.G. Sebald’s Syncretic Discourse - Pezzini, Isabella (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2008)
The article examines the interrelation of photograph and text in W.G. Sebald’s On the Natural History of Destruction (2001). This intermediality is, indeed, characteristic of Sebald’s work in both fiction and non-fiction. On the Natural History... belongs to the latter category, an involved and emotional examination of the collective repression in the consciousness of the German people of the carpet-bombing of Germany at the end of World War II. Here too the photographs have a function which goes far beyond that of testimony, the images constructing a complex plot within and with the text, on the level of both expression and content. What they produce is a new and singular “third language”, the only idiom capable of dealing with such complex issues of pain and blame, repression and memory.